The Implementation of Advance Organizer Model on Mathematical Communication Skills in terms of Learning Motivation - Putra, Fredi Ganda; Widyawati, Santi; Asyhari, Ardian; Putra, Rizki Wahyu Yunian (Universitas Islam Negeri Raden Intan Lampung, 2018)
Students’ low mathematical communication skill is influenced by several factors such as learning models applied by teachers in the classroom and the students’ learning motivation. Advanced organizer Model is appropriate to improve the students’ low ability. This study aims to determine whether: (1) there is an influence of advance organizer model toward the mathematical communication skill; (2) there is an influence of learning motivation toward the students’ mathematical communication skill, and; (3) there is an interaction between learning model and motivation toward mathematical communication skill. This research employs quasi-experimental design and the statistical analysis used is the two-ways variance with unequal cells. The result of this research shows that: (1) there is an influence of advance organizer model toward mathematical communication skill; (2) there is an influence of learning motivation toward students’ mathematical communication skill, and ; (3) there is no interaction between learning model and motivation toward mathematical communication ability.